2010
DOI: 10.1111/j.1750-3841.2009.01484.x
|View full text |Cite
|
Sign up to set email alerts
|

Water Activity and Temperature Effects on Fungal Growth and Ochratoxin A Production by Ochratoxigenic Aspergillus carbonarius Isolated from Tunisian Grapes

Abstract: This study investigated the effects of temperature (15 to 37 degrees C) and water activity (0.90 to 0.99) on the growth and production of ochratoxin A (OTA) by Aspergillus carbonarius cultured on synthetic nutrient medium (SNM) after 5 and 10 d of incubation. Total of 8 ochratoxigenic A. carbonarius, isolated from vineyards located in different regions of Tunisia, were used. Growth data were modeled by the flexible model of Baranyi and growth rates at each set of conditions were obtained. For both growth and O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 39 publications
10
24
0
Order By: Relevance
“…Moreover, our findings are in line with Lasram et al (2010) who reported a significant decrease of A. carbonarius growth when temperature increased over 37 C. Pateraki et al (2007) after assessing the germination of five A. carbonarius strains under different a w levels and NaMBS Fig. 1.…”
Section: Fungal Growthsupporting
confidence: 94%
See 2 more Smart Citations
“…Moreover, our findings are in line with Lasram et al (2010) who reported a significant decrease of A. carbonarius growth when temperature increased over 37 C. Pateraki et al (2007) after assessing the germination of five A. carbonarius strains under different a w levels and NaMBS Fig. 1.…”
Section: Fungal Growthsupporting
confidence: 94%
“…Moreover, Astoreca et al (2007) reported that the highest OTA amounts were measured at 30 C/0.99 a w when assessing two A. carbonarius strains isolated from dried grapes. The highest levels of OTA were found at 0.98 a w and decreased when a w decreased as reported by other researchers as well (Mitchell et al, 2004;Bellí et al, 2005;Medina et al, 2007;Lasram et al, 2010;Patharajan et al, 2011). After treatment with NaMBS, results showed that OTA content was enhanced even in the cases where fungal growth was delayed by the presence of the antifungal agent.…”
Section: Ota Accumulationsupporting
confidence: 80%
See 1 more Smart Citation
“…On the contrary, A. carbonarius was unable to grow in such climatic conditions. In a previous study (Lasram et al, 2010) the rare A. carbonarius strains isolated from Regueb region showed that under dry and hot conditions, they grew significantly faster than A. carbonarius strains those coming from northern regions. These isolates could have developed a tolerance towards arid climate.…”
Section: Discussionmentioning
confidence: 98%
“…Fungi were allowed to grow on a synthetic grape juice medium (SGM) at diverse mixed spore ratios (0:100, 25:75, 50:50, 75:25, and 100:0) in different temperatures (15, 20, and 25°C), water activity (aw) levels (0.95 and 0.98), and incubation time (7,14,21, and 28 days). The results obtained from this work could be useful in elucidating the role of atoxigenic fungal species and their ability to control toxigenic isolates/strains and reduce OTA production.…”
mentioning
confidence: 99%